Context specific challenges of the WHO infection prevention and control core components in the Faranah region: a mixed methods approach - Borodova, Anna; Diallo, Amadou Aziz; Songbono, Christine Timbo; Rocha, Carlos; Nabé, Ibrahima; Le Marcis, Frederic; Cherif, Mahamoud Sama; Müller, Sophie Alice (Frontiers in Public Health, 2025)
Infection prevention and control (IPC) programs have been reported to reduce healthcare associated infections by up to 70%. These rates vary globally, with scare data suggesting that the highest prevalence occurs in the African region exceeding 50% in Guinea. The Infection Prevention and Control Assessment Framework facilitates the evaluation of WHO guidelines on core components of infection prevention and control programs. Using this framework, selected healthcare facilities in Faranah, Guinea were evaluated ahead of an implementation of a training of trainer’s program. Between May 2023 and March 2024, in a mixed method approach, the core components of 25 healthcare facilities were assessed in conjunction with an evaluation of 17 trainer’s knowledge and perception on hand hygiene through standardized tools. Findings were further triangulated through a deductive analysis consisting of participant observations and semi structured interviews. The overall median of the Infection Prevention and Control Assessment Framework score in the region was basic (242.5, IQR 172.5–342.5). Lowest scores were reported for IPC education, whereas IPC guidelines and healthcare associated infection surveillance received high scores. Rural healthcare centers had the lowest score (210.0, IQR 157.5–265.0), confirmed by qualitative assessment indicating a lack of allocated budget in these facilities in addition to generally observed patient and staff overload. Participant observation found that while healthcare associated infection surveillance scored highly and IPC guidelines were displayed on posters; their practical application was rare. This was triangulated with healthcare workers self-reporting hand hygiene compliance of up to 90% whereby demonstrating considerable gaps in knowledge of WHO hand hygiene standards. Our study provides detailed understanding of a resource limited setting and highlights the importance of continuous IPC training together with behavior changes and the improvement of healthcare associated infection surveillance. In settings where a majority reside in rural areas, appointed health centers must be paid special attention to as they may often be underserved. Finally, infrastructural challenges such as the allocation of budget, patient and staff overload need to be addressed in order to improve the health and safety of patients and healthcare workers.